2019
DOI: 10.18185/erzifbed.619692
|View full text |Cite
|
Sign up to set email alerts
|

Eşdeğer Deprem Yükü Yöntemi Kullanılarak Tarihi Bir Yığma Yapının Sismik Performans Düzeyinin Belirlenmesi

Abstract: Tarih boyunca Anadolu toprakları, birçok medeniyete ev sahipliği yapmıştır. Bu sebeple ülkemizde tarihi yapılar azımsanmayacak sayıdadır. Bununla birlikte ülkemizin, aktif deprem kuşağı içerisinde yer alması sebebiyle birçok tarihi yapı, meydana gelen depremlerden zarar görmüş veya yıkılmıştır. Kültür mirası açısından önem arz eden tarihi yapılarımızın, gelecek kuşaklara güvenle aktarılabilmesi için sismik performans seviyelerinin doğru ve hızlı bir şekilde belirlenerek gerekli müdahalelerin yapılması oldukça … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This masonry bath is a rare historic building that survived the strong ground motions like the 1939 and 1992 earthquakes, which caused the collapse of many buildings, including historic buildings in Erzincan [13][14][15]. Although there are many studies in the literature investigating the seismic performances of historical masonry structures such as mosques, churches and walls [16][17][18], studies analyzing historical baths are limited [19][20]. The main purpose of this study is to investigate how Çadırcı Bath resists these intensive earthquakes and also to evaluate the importance of the structural configuration on the seismic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…This masonry bath is a rare historic building that survived the strong ground motions like the 1939 and 1992 earthquakes, which caused the collapse of many buildings, including historic buildings in Erzincan [13][14][15]. Although there are many studies in the literature investigating the seismic performances of historical masonry structures such as mosques, churches and walls [16][17][18], studies analyzing historical baths are limited [19][20]. The main purpose of this study is to investigate how Çadırcı Bath resists these intensive earthquakes and also to evaluate the importance of the structural configuration on the seismic resistance.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the analyses, they observed that the possible crack zones occurring in the Mosque were similar to the crack zones occurring in the Mosque after the 2020 Sivrice-Elazığ earthquake. Kumbasaroğlu and Çelik [12] analyzed the historical Yanıkoğlu Mosque under self-weight and earthquake forces calculated according to the equivalent earthquake load method. As a result of the analysis, they determined the performance level of the structure as limited damage.…”
Section: Introductionmentioning
confidence: 99%
“…Kumbasaroglu and Celik calculated the earthquake load that a historic masonry building can be exposed to using the Equivalent Earthquake Load Method. They examined the linear performance of the structure exposed to earthquake load (Kumbasaroglu and Celik, 2019). Ucar and Merter produced spectrum curves to be used for Equivalent Earthquake Load Method and Mode Combination Method from real earthquake records.…”
Section: Introductionmentioning
confidence: 99%